The asylum process in the UK and its impact upon mental health of asylum seekers and refugees between 2020 to 2022 - Harding, Oliver (2022)
In March 2022 the refugee crisis has been raised in everyone’s collective consciousnesses as 10 million refugees fled from Ukraine. The Russian invasion of Ukraine has highlighted the disparity in which refugees from different backgrounds are treated in Europe and in the United Kingdom. Prior to the invasion 1% of the world population were refugees or Internally Displaced Persons, IDP. The UNHCR observed that by June the number of forcibly displaced worldwide had increased to nearly a 100 million. In the United Kingdom many refugees face an indeterminate period of time in accommodation before being given ‘leave to remain.’ The process preceding the decision by the Home Office effectively places the refugees lives on hold. The outcome for them is unknown. The process of dealing with The Home Office and Migrant Help is protracted and frustrates many refugees. It is not unusual for refugees to be in temporary accommodation for more than a year. Mental health is affected by indeterminate stay in hotel accommodation. Even the most resilient refugees find the process challenging. The Covid-19 pandemic has made this situation worse. Suicides are not uncommon. Suicides and the threat of suicide have been brought to the fore by the first planned deportation flights to Rwanda in June 2022.